An Overview of Biosensors Based on Glutathione Transferases and for the Detection of Glutathione. Issue 8 (28th June 2021) - Federici, Luca; Masulli, Michele; Allocati, Nerino
Abstract: Glutathione transferases are enzymes involved in the detoxification against xenobiotics and noxious compounds. These enzymes catalyse a variety of reactions on many physiological and xenobiotic compounds using glutathione as a co‐substrate. Moreover, many compounds are inhibitors of such enzymes. A wide array of biosensors based on glutathione transferases have been developed for analysing a variety of noxious compounds, as well as several biosensors devoted to the detection and quantification of glutathione and of glutathione transferases themselves. Here, we review the state of the art in this active field of research, highlighting the possible applications of such devices. Abstract :